Splenic diffuse red-pulp small B-cell lymphoma associated with hepatitis B virus: a report of two cases - Kerbauy, Mariana Nassif (2016)
CONTEXT: Splenic diffuse red-pulp small B-cell lymphoma is a rare disease, representing less than 1% of all non-Hodgkin lymphomas (NHL). This entity is characterized by involvement of bone marrow sinusoids and peripheral blood. The majority of cases are at an advanced stage when diagnosed. Its pathogenesis is still poorly understood. CASE REPORTS: We report on two patients with chronic non-replicating hepatitis B virus (HBV) who developed splenic diffuse red-pulp small B-cell lymphoma. Both of them were in stage IV at diagnosis and evolved with aggressive disease. Both of them achieved a complete response through chemotherapy, but one of them died due to infectious complications during bone marrow transplantation. The other decided not to undergo transplantation and continues not to show any evidence of disease today (three years after treatment). Some studies have shown a possible association between B-cell NHL and HBV. Nonetheless, the mechanism through which this oncogenic virus interacts with B-cell NHL is still poorly understood. HBV is lymphotropic and may insert into the host’s genome, thus causing overexpression of oncogenes and downregulation of tumor suppressor genes. Therefore, chronic stimulation by HBV can increase B-cell proliferation, which promotes monoclonal expansion of these cells and results in malignancy. CONCLUSION: HBV may be implicated in the pathogenesis of this lymphoma, although no direct association between these two entities could be proved in the present study. Further investigations are necessary.